2018
DOI: 10.1017/s0022029918000377
|View full text |Cite
|
Sign up to set email alerts
|

Early weaning and high feeding level in post-weaning period did not impact milk production in Alpine dairy goats

Abstract: The experiment reported in this Research Communication aimed to determine the combined effects of early weaning and post-weaning feeding level on growth, reproductive parameters and milk yield in Alpine goats. Sixty-four Alpine goat kids were weaned abruptly at either 12·2 (±1·40) kg (40 d of age, E) or 17·7 (±2·30) kg (60 d of age, No). After weaning, E and No goats were subjected to 2 feeding strategies (n = 16): ad libitum concentrate until 130 d of age and then 620 g DM/d/goat until 200 d of age (EC and No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Therefore, we could assume that the kids ate enough concentrate before weaning not to exhibit weaning shock. Indeed, Panzuti et al observed no weaning shock after having weaned Alpine goats at 12 kg and 40 days of age as shown also by Ferreira and Thornton (2004) in Saanen kids weaned at 42 days of age (Panzuti et al 2018). We could assume that the improvement of feed quality (milk replacer and concentrate), since 1980, had a beneficial impact on solid feed intake.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Therefore, we could assume that the kids ate enough concentrate before weaning not to exhibit weaning shock. Indeed, Panzuti et al observed no weaning shock after having weaned Alpine goats at 12 kg and 40 days of age as shown also by Ferreira and Thornton (2004) in Saanen kids weaned at 42 days of age (Panzuti et al 2018). We could assume that the improvement of feed quality (milk replacer and concentrate), since 1980, had a beneficial impact on solid feed intake.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, an ad libitum feeding from weaning to parturition highly reduced milk production in first lactation compared to restricted feeding management in Alpine goats (Aubry et al 2012). On the contrary, milk production was not affected by a high feeding level of the same concentrate from weaning until the mating period in another experiment performed in the same laboratory (Panzuti et al 2018). The only difference between the two studies was the duration of the ad libitum feeding period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is similar to conditions in early lactation when nutrient and energy intake are less than needed to support milk production, resulting in limited levels of short and medium chain FA in milk and elevated concentrations of long chain FA, primarily C18:0 (stearic acid) and C18:1 (oleic acid), arising from mobilized tissue (Eknaes and Skeie 2006). Panzuti et al (2018) conducted a study addressing potential for adverse effects of high nutritional planes for Alpine doelings during growing on subsequent milk yield as has been observed in dairy cattle. Doelings were weaned at 40 or 60 days of age and offered concentrate ad libitum until 200 days when breeding began or restricted from day130 to 200.…”
Section: Production Systemmentioning
confidence: 68%